2001
DOI: 10.4278/0890-1171-15.5.296
|View full text |Cite
|
Sign up to set email alerts
|

Financial Impact of Health Promotion Programs: A Comprehensive Review of the Literature

Abstract: There are good correlational data to suggest that high levels of stress, excessive body weight, and multiple risk factors are associated with increased health care costs and illness-related absenteeism. The associations between seat belt use, cholesterol, diet, hypertension, and alcohol abuse and absenteeism and health care expenditures are either mixed or unknown. Health promotion programs are associated with lower levels of absenteeism and health care costs, and fitness programs are associated with reduced h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
322
4
28

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(366 citation statements)
references
References 74 publications
12
322
4
28
Order By: Relevance
“…Health Care Costs A number of health risk factors have been shown to be associated with higher health care costs (Table 1). The presence of multiple risk factors provides a better prediction of future costs than any single factor (Aldana 2001). Studies by Yen et al (1991) established annual health care costs associated with multiple risk factors.…”
Section: Risk Factor Reduction Cost Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Health Care Costs A number of health risk factors have been shown to be associated with higher health care costs (Table 1). The presence of multiple risk factors provides a better prediction of future costs than any single factor (Aldana 2001). Studies by Yen et al (1991) established annual health care costs associated with multiple risk factors.…”
Section: Risk Factor Reduction Cost Analysismentioning
confidence: 99%
“…This review also concluded that health promotion programs are associated with reduced health care costs (Aldana 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Varias revisiones de la literatura soportan que estudios experimentales o cuasiexperimentales sobre programas de salud basados en cambios de estilos de vida y que utilizan comunicación y consejos individualizados en trabajadores de alto riesgo producen un retorno económico positivo al empresario 5,7-10. La literatura también destaca que muchos de los estudios que tuvieron resultados negativos eran de poca calidad científica (no eran estudios randomizados ni experimentales con presencia de varios sesgos; el más común el sesgo de selección entre el grupo que recibía el programa de salud y el grupo control) 5,8 .…”
unclassified
“…Both the nature of the findings and the overall quality of the literature were evaluated in an attempt to answer two questions: Do individuals or populations with high health risks have worse financial outcomes than individuals or populations with low health risks? Aldana (2001) found that health promotion programs were associated with lower levels of absenteeism and healthcare costs, while fitness programs are associated with reduced healthcare costs. 10 Fries et al (1993) performed a study of 4,712 Bank of America retirees to evaluate the effectiveness of a health promotion program in terms of health risk reduction and reduction in medical costs.…”
Section: Increasing Popularity Of Wellness Programsmentioning
confidence: 98%
“…Aldana and Pronk (2001) conducted a review of literature and found that health promotion programs can lead to a reduction in healthcare costs and reduced absenteeism by up to 20%. Aldana (2001) reviewed 72 studies to summarize the literature on health promotion programs and their impact on employee-related healthcare expenditures and absenteeism. Both the nature of the findings and the overall quality of the literature were evaluated in an attempt to answer two questions: Do individuals or populations with high health risks have worse financial outcomes than individuals or populations with low health risks?…”
Section: Increasing Popularity Of Wellness Programsmentioning
confidence: 99%